Therapeutic innovations in triple negative breast cancer: integrating molecular targeting and monoclonal antibody strategies - Mir, Prince Ahad; Kumar, Nishant; Gupta, Sukesh K.; Kaur, Anureet; Farooq, Saeema; Sandhu, Gurpreet S.; Kumar, Anoop (Frontiers in Oncology, 2025)
Triple Negative Breast Cancer (TNBC) is a specific kind of breast cancer that is distinguished by the lack of expression of three specific receptors, namely human epidermal growth factor receptor 2 (HER2), estrogen receptor (ER), and progesterone receptor (PR) and are common in women under 40, especially among African American population or those with a BRCA1 genetic mutation. TNBC is characterized by its very aggressive behavior, elevated rates of recurrence, and restricted therapy alternatives in comparison to other subtypes of breast cancer. Chemotherapy is considered the most widely employed therapy against TNBC but experiences off-target toxicity due to its non-selectivity. Such a scenario led to the genetic profiling of the TNBC patients, which led to the identification of several targets and signaling pathways that can be considered as a therapeutic focus for the treatment of TNBC. In this review, we have compiled various therapeutic targets, including androgen receptor (AR) and PI3K/AKT/mTOR, Notch, Wnt/β-catenin, Hedgehog, and TGF-β signaling pathways, which are responsible for the progression of TNBC. In the current therapeutic landscape, the strategic targeting of key signaling pathways, coupled with the development of monoclonal antibody (mAb)-based immunotherapeutic interventions, has emerged as a promising and clinically relevant approach for the management of triple-negative breast cancer (TNBC). The mAbs reduce tumor development, modulate immune responses, and regulate the tumor microenvironment. This review summarizes their mechanisms, signaling pathway targets, clinical applications, and current therapeutic challenges.